Dose–response effect of a novel functional fibre, PolyGlycopleX®, PGX®, on satiety - Solah, Vicky; Brand-Miller, J.; Atkinson, F.; Gahler, R.; Kacinik, V.; Lyon, M.; Wood, S. (Elsevier BV, 2014)
The objective of this research was to determine the dose–response effects of a palatable, viscous and gel forming fibre, PolyGlycopleX® (PGX®), [(a-D-glucurono-a–manno-ß-D-manno-ß-D-gluco), (a-Lgulurono-ß-D mannurono), (ß-D-gluco-ß-D-mannan)] on satiety, and to gain insight into the underlying mechanisms that lead to appetite inhibition. Healthy subjects (n = 10), aged between 20.3 and 29.2 years, consumed PGX®, in granular form at 2.5, 5.0 and 7.5 g, and a 5g inulin control, with a standard breakfast. The PGX® doses of 2.5 and 7.5 g mixed with water at the start of breakfast increased satiety (iAUC of 140.0 and 157.7,P = 0.025 and 0.001, respectively) compared to the control. The most effective dose (7.5g) was palatable and corresponded to a 34% increase in fullness, measured using a visual analogue scale and incremental area under the curve, and resulted in a delayed postprandial glycaemic response when compared with the control.